2018
DOI: 10.1002/psp4.12346
|View full text |Cite
|
Sign up to set email alerts
|

Semimechanistic Population Pharmacokinetic Model to Predict the Drug–Drug Interaction Between S‐ketamine and Ticlopidine in Healthy Human Volunteers

Abstract: Low‐dose oral S‐ketamine is increasingly used in chronic pain therapy, but extensive cytochrome P450 (CYP) mediated metabolism makes it prone to pharmacokinetic drug‐drug interactions (DDIs). In our study, concentration‐time data from five studies were used to develop a semimechanistic model that describes the ticlopidine‐mediated inhibition of S‐ketamine biotransformation. A mechanistic model was implemented to account for reversible and time‐dependent hepatic CYP2B6 inactivation by ticlopidine, which causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…However, since CYP3A4 is more abundant than CYP2B6, CYP3A4 is considered to be the main CYP subtype in this metabolic pathway. Ashraf et al report that CYP2B6 is the main enzyme responsible for ketamine metabolism [29].…”
Section: Metabolitesmentioning
confidence: 99%
“…However, since CYP3A4 is more abundant than CYP2B6, CYP3A4 is considered to be the main CYP subtype in this metabolic pathway. Ashraf et al report that CYP2B6 is the main enzyme responsible for ketamine metabolism [29].…”
Section: Metabolitesmentioning
confidence: 99%
“…35 A CYP2D6 inhibitor (ticlopidine) conversely slowed metabolism of IV esketamine, though any relevance to the intranasal preparation is unclear. 36 An in vitro study of esketamine showed modest induction of CYP2D6 and 3A4. 11 The mean terminal half-life for esketamine ranges between 7 and 12 h, though there is a period of rapid decline in plasma concentrations over 2-4 h following the C max .…”
Section: Therapeutic Advances In Drug Safety 11mentioning
confidence: 99%
“… 35 A CYP2D6 inhibitor (ticlopidine) conversely slowed metabolism of IV esketamine, though any relevance to the intranasal preparation is unclear. 36 An in vitro study of esketamine showed modest induction of CYP2D6 and 3A4. 11…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Population models were specified with differential equations that were solved with ADVAN13 subroutine and parameters estimated using first-order conditional estimation with interaction. A sequential PK-PD approach was used as described previously [23,24]. In the first step, a PK model was developed using IV administration data only, followed by the implementation of a semi-mechanistic absorption model for SC administration.…”
Section: Model Developmentmentioning
confidence: 99%